Research on Modern Power Spectral Estimation on Radar Velocity Measurement - MEI Jialun; WANG Xiao; BAO Yansheng (机车电传动)
Radar velocity measurement was widely used in the rail transit, while the algorithm was the key to the system. Relevant contents of the classical power spectral estimation and modern power spectral estimation were introduced, the latter was expounded emphatically. Through the simulation with Matlab, and by observing and analyzing signal waveform and power spectrum, the feasibility of the theory was verified. At last, the algorithm was successfully run on target object to measure the velocity by analyzing the radar sensor output signal.